Analysis of armature winding open‐phase fault in multi‐phase annular brushless exciter at nuclear power plant. Issue 3 (16th January 2021) - Chen, Jianlin; Hao, Liangliang; Wang, Xiaoming; Guo, Lixiong; Xiong, Xin; Wei, Yubang; Li, Wenwu; Yang, Deguang
Abstract: The multi‐phase annular brushless exciter (MPABE) of nuclear power plants has suffered numerous armature winding open‐phase faults (AWOPF) in the field operation. In order to achieve reliable protection of the MPABE, its AWOPF is systematically studied through theoretical analysis, simulation calculation and model machine experiments. First, proceeding from the armature current waveform in normal operation and the influence of the AWOPF on it, the armature reaction magnetomotive force (MMF) is analysed deeply. Then, the theoretical analysis about the harmonic electromotive force (EMF) induced by armature reaction MMF on the field winding is presented, obtaining the harmonic characteristics of field current: the even‐order field harmonic currents increase obviously under the AWOPF. Finally, correlate experiments and simulations were performed on a customized experimental prototype. The experimental and simulation results are consistent and verify the conclusion of the theoretical analysis, which can serve as a theoretical basis for the monitoring and diagnosis method of the AWOPF in the MPABE.